Color Image Hiding In Cover Speech Signal By Using Multi-resolution Discrete Wavelet Transform - Muraab, Lecturer Dr. Samir J.AL-; AL-Mayaly, Asst. lecturer Haider I. (Iraqi Journal for Electrical and Electronic Engineering, 2009)
Data hiding, a form of steganography, embeds data into digital media for the purpose of identification, annotation, security, and copyright. The goal of steganography is to avoid drawing suspicion to the transmission of a hidden message. Digital audio provides a suitable cover for high-throughput steganography. In this paper a high robustness system against the attackers in hiding of color images is presented. We used the multi-resolution discrete wavelet transform in hiding process. The JPEG format type for color images and WAV format for speech cover signal that used in test of system. Programs and graphics are executed by using MATLAB version 6.5 programs.